Development, Mobilization and War: The Iranian Construction Jehad, Construction Mobilization and Trench Builders Association (1979–2013). Issue 1 (2nd January 2017) - Lob, Eric
Abstract: Based on ethnographic and archival research in Iran, this article examines the intersection of war making, rural development and popular mobilization in the state formation of the Islamic Republic of Iran (IRI). To this end, the article profiles three organizations that were instrumental to this process: The Construction Jehad, the Construction Mobilization and the Trench Builders Association. During the last three decades, these organizations have helped the IRI and its factionalized elites in their attempts to promote rural development, mobilize and socialize constituents, gain popular support and electoral votes, and demobilize and marginalize domestic and foreign opponents. These organizations also produced and addressed the unintended consequences of cognitive dissonance, deep-seated disillusionment and ideological detachment among activists, veterans, students and youth. By organizing a critical mass of constituents and aggregating popular claims from below, these organizations exerted bottom-up pressures and demands on the very state and the very elites that they had assisted and supported.